GgtreeExtra: Compact Visualization of Richly Annotated Phylogenetic Data. (7th June 2021) - Xu, Shuangbin; Dai, Zehan; Guo, Pingfan; Fu, Xiaocong; Liu, Shanshan; Zhou, Lang; Tang, Wenli; Feng, Tingze; Chen, Meijun; Zhan, Li; Wu, Tianzhi; Hu, Erqiang; et al.
Abstract: We present the ggtreeExtra package for visualizing heterogeneous data with a phylogenetic tree in a circular or rectangular layout (https://www.bioconductor.org/packages/ggtreeExtra ). The package supports more data types and visualization methods than other tools. It supports using the grammar of graphics syntax to present data on a tree with richly annotated layers and allows evolutionary statistics inferred by commonly used software to be integrated and visualized with external data. GgtreeExtra is a universal tool for tree data visualization. It extends the applications of the phylogenetic tree in different disciplines by making more domain-specific data to be available to visualize and interpret in the evolutionary context.